Towards meaningful community ambulation in individuals post stroke through use of a smart hip exoskeleton: A preliminary investigation. - Herrin, Kinsey; Upton, Emily; Young, Aaron (Assistive Technology, 2024)
Stroke is the leading cause of long-term disability in the United States, leaving survivors with profound mobility challenges that impact independent community ambulation. Evidence shows assistance at the hip during walking may be beneficial for stroke survivors. In this cross-over design study, we examine the impact of a novel hip exoskeleton on both functional and patient reported outcomes measuring speed, fall risk, gait symmetry, energy expenditure and perceived walking ability during both indoors and outdoors in single and serial counting dual task paradigms. Nine ambulatory stroke survivors with hemiplegia were included. No differences were seen between the exoskeleton and baseline conditions for any outcomes. Only the patient reported outcome in which subjects were asked to rate their ability to walk outdoors approached statistical significance (p = 0.051) with greater improvement reported for the exoskeleton condition. When asked to rate several key factors about the exoskeleton, weight and assistance emerged as primary perceived negative factors of the exoskeleton underscoring the need for improvements to the technology in this area. Despite lack of differences across groups, some individuals responded positively to the exoskeleton for several functional outcomes measured, highlighting the need for additional exploration into the use of personalized hip exoskeletons for post-stroke rehabilitation.